(untitled) (Perioperaciina Medicina, 2023)
Introduction. Nosocomial infections are risk factors associated with in-hospital mortality. Among other factors, these infections are strongly associated with invasive devices. In pediatric patients, a central venous catheter (CVC) is one of the most common causes of catheter-related bloodstream infection (CRBSI). Background. To investigate the effectiveness of antimicrobial chlorhexidine dressings compared with standard dressings in the prevention of central venous catheter-related bloodstream infections. Methods. 20 children who were treated in the intensive care unit were randomly divided into two groups of 10: a group that used chlorhexidine dressings and a group that used standard dressings (comparison group). Patient care was carried out in accordance with asepsis and antisepsis rule. The primary outcomes were a comparative study of microbiological researches of peripheral blood blood culture and catheter blood sample. But the final results were cultures from the tip of the catheter (at least 5 cm) after removal of the catheter in case of clinical symptoms of KAIK or in case of planned removal of the catheter due to the lack of its further need. Results. Catheter colonization occurred in 3 patients in the control group (3 %) and in 2 patients in the chlorhexidine dressing group (2 %). Catheter-related bloodstream infections occurred in 3 patients in the control group (3%), and in patients in the chlorhexidine group, no microorganisms were isolated by microbiological examination of the implantation sites (0 %). Although more patients in the comparison group had catheter-related bloodstream infections, the difference in infection rates between the two groups was insignificant (P = 0.07). Conclusions. The use of chlorhexidine-impregnated dressings reduced the incidence of catheter-related bloodstream infections, contamination, colonization, and local catheter infection in the pediatric intensive care unit, but there was no significant difference compared with the use of standard dressings. This study needs further study in pediatric patients.